Improvement of Losartan Transdermal Permeation using Oleic Acid Pretreatment: in Vitro Observation and in Vivo Prediction - Binarjo, Annas; Nugroho, Akhmad Kharis (UI Scholars Hub, 2019)
The effect of oleic acid on losartan transdermal permeation has been observed to explore its ability as chemical enhancer. Potassium losartan solutions in citric buffer pH 5.0 were made in two levels of concentration i.e. 2 mg/mL and 10 mg/mL using propylene glycol 15% as solubilizing agent. Losartan transport from such solutions with and without oleic acid one hour pretreatment were tested using male Wistar rat skin as a membrane for 30 hours in vertical diffusion sel. The transport profiles were analyzed based on the lag time diffusion method. It is showed that oleic acid pretreatment did not effect on losartan permeation rate and efficiency of 2 mg/mL potassium losartan concentration. However, such pretreatment enhanced losartan permeation rate and efficiency 21 and 23-fold higher respectively for 10 mg/mL the potassium losartan concentration. It is predicted that losartan minimum effective plasma concentration can be achieved in transdermal administration through this transport improvement in normal application area.